KETOKSIKAN AKUT EKSTRAK AIR Eupatorium riparium Reg. PADA TIKUS SPRAGUE-DAWLEY - Nurlaila Nurlaila; Sita Rina Widyarini; Subagus Wahyuono; Lukman Hakim (Majalah Obat Tradisional, 2015)
Eupatorium riparium Reg. is one of medicinal plant that might be used to cure a disease optimally. Some research reports and traditional uses in society show that this plant can  be used as a diuretic, anti-inflammatory, hepatoprotective, immunostimulant, anti-malarial, and anti-infective agents. Therefore, it is necessary to evaluate its safety. The aim of this study is to determine the acute toxicity of the aqueous extract of E. riparium Reg. at Sprague-Dawley (SD) rats. The acute toxicity test was conducted using the method of OECD 423. Male SD rats were orally given aqueous extracts of E. riparium Reg. which was started with a dose of 2000 mg / kg. Observations were performed 24 hours after the administration with intensive observations on the first 4 hours. The result showed that there were no animals found in dead condition when treated with a dose of 2000 mg/kg; repeated testing is also showed that no animals died, so the observation was continued until 14 days. The dose was increased to 5000 mg/kg, and again there were no dead animals. From the results, it can be concluded that the potential for acute toxicity (LD50) (cut off) of aqueous extract of E. riparium Reg., in rats is > 5000 mg/kg. In addition, toxic symptoms such as restlessness, lick, hyperactivity, forced movement, paralysis of the  legs, dyspnea were shown but these symptoms were disappeared after 14 days. Histopathological study showed that there was no change on animal’s organ compared to the normal control.